Thin-Skinned Tectonics of the Tansen-Pokhara Section, Central Nepal Himalaya - Paudel, Lalu Prasad (Journal of Natural History Museum, 2015)
Geological field survey and structural analysis were carried out in the Tansen-Pokhara section of central Nepal in an attempt to unravel the thin-skinned tectonic geometry of the Lesser Himalaya. The Lesser Himalaya in the area forms a foreland-propagating duplex structure, each tectonic unit being a horse bounded by imbricate faults. The Upper Main Central Thrust and the Main Boundary Thrust are the roof and floor thrusts, respectively. The Bari Gad-Kali Gandaki Fault is an out-of-sequence fault. The Pindi Khola Fault is an antithetic back-thrust developed on the hangingwall of the Bari Gad-Kali Gandaki Fault, and the Kusma Fault is a splay-off of the Phalebas Thrust. Deformation of the Lesser Himalaya occurred in distinct three phases namely pre-Himalayan, Eohimalayan and Neohimalayan. The duplex structure was formed in the Neohimlayan stage in the period between Middle Miocene and Early Pleistocene. J. Nat. Hist. Mus. Vol. 26, 2012: 15-28